Equality and System of inheritance - Alami, Abdullah (Journal of Humanities & Social Sciences, 2019)
This is a research on inheritance legislation and its system, through which we tried to raise the most important issues that are raised around it, studying these problems by analyzing structured text messages and deconstructing their structure.
Keywords: inheritance; equality; legislation; communication